INTENTION TO BUY AMBON CITY COMMUNITIES: CHOICE OF E-COMMERCE PLATFORMS AND DETERMINING FACTORS - Merry M. Pelupessy; Aisah Asnawi; Etvin R. Tamher; Evracia Turukay (SEAN Institute, 2023)
The purpose of this study was to examine the effect of visual merchandising and product variety on buying interest in the Tokopedia.com e-commerce fashion sector. This study uses a quantitative descriptive methodology. The population used is consumers from Tokopedia.com. In this study, 115 respondents were sampled using a questionnaire as a tool for collecting data. Purposive sampling technique and non-probability sampling technique were used for sampling. Multiple linear regression is a data analysis technique and SPSS version 25 analysis tool used in this study. Based on the results of multiple regression analysis, the visual merchandising variable (X1) has a significant and positive effect on the purchase intention variable (Y). This is evidenced by the results of multiple linear regression testing which was obtained at 0.974. Furthermore, the product variation variable (X2) has a positive and significant influence on Purchase Intention (Y). This is proven by the results of multiple linear regression testing of 0.395. While the promotion variable (X3) has a positive and significant influence on the Purchase Interest variable (Y) as evidenced by the sig value (0.006) and is less than 0.05. Visual merchandising variables have a greater influence on purchase intention, product variety variables have an influence on purchase intention, and promotion variables have an influence on purchase intention.